Towards Actualizing the Value Potential of Korea Health Insurance Review and Assessment (HIRA) Data as a Resource for Health Research: Strengths, Limitations, Applications, and Strategies for Optimal Use of HIRA Data - Kim, Jee-Ae (J Korean Med Sci, 2017)
Health Insurance and Review Assessment (HIRA) in South Korea, also called National Health Insurance (NHI) data, is a repository of claims data collected in the process of reimbursing healthcare providers. Under the universal coverage system, having fee-for-services covering all citizens in South Korea, HIRA contains comprehensive and rich information pertaining to healthcare services such as treatments, pharmaceuticals, procedures, and diagnoses for almost 50 million beneficiaries. This corpus of HIRA data, which constitutes a large repository of data in the healthcare sector, has enormous potential to create value in several ways: enhancing the efficiency of the healthcare delivery system without compromising quality of care; adding supporting evidence for a given intervention; and providing the information needed to prevent (or monitor) adverse events. In order to actualize this potential, HIRA data need to actively be utilized for research. Thus understanding this data would greatly enhance this potential. We introduce HIRA data as an important source for health research and provide guidelines for researchers who are currently utilizing HIRA, or interested in doing so, to answer their research questions. We present the characteristics and structure of HIRA data. We discuss strengths and limitations that should be considered in conducting research with HIRA data and suggest strategies for optimal utilization of HIRA data by reviewing published research using HIRA data.